Faktor Pengambilan Keputusan Hedging Dengan Menggunakan Instrumen Derivatif Valuta Asing Pada Perusahaan Manufaktur: Hedging Decision-Making Factors Using Foreign Currency Derivative Instruments in Manufacturing Companies - Arief Yuswanto Nugroho,; Agus Wiastono,; Anudiyan Amir Mas'ud, (JOURNAL KOPERASI DAN MANAJEMEN, 2022)
Hedging is an alternative to risk management that aims to protect the assets of a company from losses caused by the risk. This research aimed to analyze the influence of corporate value, liquidity, leverage, growth opportunity, financial distress, and firm size on the hedging decision of manufacturing companies listed on Indonesia Stock Exchange. The samples were 24 manufacturing companies that were listed on Indonesia Stock Exchange from 2020 to 2021 which had been selected by using the purposive sampling technique. The data analysis technique used logistic regression. The research result showed that corporate value, liquidity, and growth opportunity did not give any significant influence on the hedging decision whereas leverage, financial distress, and firm size had a significant influence on the hedging decision.